An Analysis of the Protected Area Planning and Management Frameworks - Rallan, Pallavi (International Journal of Membrane Science and Technology, 2023)
Wildlife tourism is a significant contributor to many economies around the globe. Hence, effective planning and management of the protected areas that provide recreational opportunities in wildlife tourism is essential to ensure sustainable tourism practices. Over the years, several frameworks have been developed for protected area planning and management. This paper critically analysis a few of those frameworks on their origin, processes, strengths, and weaknesses. As a result, the paper highlights the common themes among the frameworks along with their limitations and scope for future research.